The Effects of Citrullus Colocynthis (L.) Hydroalcoholic Extract on the Function of Lymphocyte Proliferation and Innate Immune System Responses after Challenge with the REV1 Vaccine in Wistar Rats - Meysam Abtahi Froushani; Saeed Nafisi; Hadi Esmaili Gourvarchin Galeh; Bahman Mansori Motlagh; Muhammad Seddigh Shahryari Nor (Fasa University of Medical Sciences, 2016)
Background & Objectives: The main objective of this study is to determine the possible effects of hydroalcoholic extract of Citrullus Colocynthis on the humoral and cellular immune responses in Wistar rats after challenge with REV-1 vaccine. Materials & Methods: The studied population included 20 male rats that were randomly divided into two equal groups and were immunized with Rev1 vaccine (0.1 ml Rev1+0.9 ml PBS (. Treatment group received hydroalcoholic extract of the C. colocynthis (50 mg/kg) orally every day from the beginning of the study and it continued for two weeks. Blood sampling was performed five days after the last injection. Moreover, 48 hours before blood sampling, Rev1 vaccine (0.1 ml Rev1+0.9 ml PBS (was injected into the left foot of rats. The levels of anti-Rev1 antibody and the specific cellular immune responses were measured by sero-agglutination test, footpad thickness, and griess colorimetric method, respectively. Lymphocyte proliferation, nitric oxide production, respiratory burst, and phagocytosis in splenocytes were determined by MTT test, Griess test, NBT assay, and slide test, respectively. Results: The levels of anti-Rev1 antibody, phagocytosis and Lymphocyte proliferation index in splenocytes were increased in treatment group compared to control group. Nevertheless, the levels of the cellular immunity (food pad thickness), NBT, and Nitric oxide in treatment group showed a significant decrease compared to control group (p<0/05). Conclusion: The hydroalcoholic extract of C. colocynthis may be used as a natural source for modulating the immune system